AN APPLICATION OF MAMDANI IN SELECTING MAJORS IN HIGHER EDUCATION - Heni Hapsari; Muhammad Dzulfikar Fauzi; Shofwatul Uyun (IJID (International Journal on Informatics for Development), 2013)
The election for a right major at university will make a big difference because students should choose a major that suits their basic skills and talent preference. A research case uses a sample from various majors in state university in Indonesia. There are 29 majors available. Therefore, interest score, talent score, and basic ability score become a consideration matter in choosing the right major for them. The implementation of this system uses PHP programming language and MySQL database which based on the web. This research uses sample data of SMAN (state high school) 1 on Kutowinangun, Kebumen. It is including self-data, interest score, talent score, and basic skill score. This research uses a fuzzy inference system using Mamdani method. Mamdani method works based on linguistic principle and has a fuzzy algorithm which supply approximation to be entered by mathematic analysis. Data are processed through the calculation phase of fuzzy and result given by the system is a recommendation of a major suggested to be taken by the student. This system shows a recommendation of a major that suits the student. This system also gives information about universities which provide recommended major. This system is hope to help students in choosing their major.